EMPOWERING STUDENTS’ LANGUAGE COMPETENCE AND CULTURAL AWARENESS THROUGH COMMUNICATIVE APPROACH - Mantra, Ida Bagus Nyoman; Maba, Wayan; Wedasuwari, Ida Ayu Made; Staupelyte, Agne (Bajang Institute, 2024)
The communicative approach to learning language aims to improve students' communication skills, both orally and in writing. This approach focuses on developing four language skills: listening, reading, speaking, and writing. In the communicative approach, students can use language actively in communicative situations. This study used classroom action research to improve students' language competence and cultural awareness by implementing a communicative approach. Data from the study were collected through pretest, post-test, and questionnaire. The results showed that the student's language competence and cultural awareness improved significantly through a communicative approach. Therefore, communicative learning is effective for improving language competence and cultural awareness. This study implies that teachers should consider using a communicative approach in developing students’ language competence and cultural awareness.